1973
DOI: 10.1073/pnas.70.10.2850
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of DL-Tryptophan by Affinity Chromatography on Bovine-Serum Albumin-Agarose Columns

Abstract: Bovine-serum albumin, known to have antipodal specificity in the binding of tryptophan, was selected as the affinity chromatographic matrix for the attempted chromatographic resolution of DL-tryptophan. Complete resolution was accomplished when DL-tryptophan was chromatographed on bovine-serum albuminsuccinoylaminoethyl-Sepharose.Resolution of optical isomers by conventional methods is frequently laborious and incomplete. The mechanical and chemical methods are empirical in nature, and in practice choosing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(27 citation statements)
references
References 15 publications
(9 reference statements)
1
25
0
1
Order By: Relevance
“…However, [benzene ring U-14C]tryptophan was available only as the racemic mixture. This was resolved by exploiting the stereo-specific binding of tryptophan to serum albumin, by the following modification of the method of Stewart & Doherty (1973), using immobilized bovine serum albumin. Cyanogen bromideactivated CH Sepharose 4B (Pharmacia Ltd) was swollen in 1 mM-hydrochloric acid and was then washed on a sintered-glass disk with 1 mM-HC1.…”
Section: Methodsmentioning
confidence: 99%
“…However, [benzene ring U-14C]tryptophan was available only as the racemic mixture. This was resolved by exploiting the stereo-specific binding of tryptophan to serum albumin, by the following modification of the method of Stewart & Doherty (1973), using immobilized bovine serum albumin. Cyanogen bromideactivated CH Sepharose 4B (Pharmacia Ltd) was swollen in 1 mM-hydrochloric acid and was then washed on a sintered-glass disk with 1 mM-HC1.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with cell-free extracts have shown that, in addition to enzymes required for the kynurenine pathway, the liver possesses the necessary enzymic complement for the catabolism of tryptophan by each of the other three pathways (Weissbach et al, 1959;Civen & Knox, 1959;Renson et al, 1966 Radiolabelled DL-tryptophan was resolved optically, and L-l5-3Hltryptophan repurified, by affinity chromatography on bovine serum albuminSepharose 4B as described by Stewart & Doherty (1973). The sources of all other materials are detailed in Smith & Pogson (1980).…”
mentioning
confidence: 99%
“…The application of immobilised serum proteins as chiral selectors stems from the seminal 1973 work of Stewart and Doherty, 27 who were able to resolve the two antipodes of tryptophan on a bovine-serum albumin (BSA)-sepharose column, in agreement with the stereoselectivity previously observed for the in vitro binding of tryptophan to BSA. Later, other groups 28,29 used BSA-and HSA-based sepharose columns to separate drug enantiomers (such as warfarin and benzodiazepines) and to determine binding constants for a variety of ligands, including fatty acids, steroids, and drugs.…”
Section: Immobilized Protein Stationary Phase (Csp) As a Rapid Tool Tmentioning
confidence: 53%